A model for the prediction of breathiness in vowels - Shrivastav, Rahul (Acoustical Society of America, 2011)
The perception of breathiness in vowels is cued by multiple acoustic cues, including changes in aspiration noise (AH) and the open quotient (OQ) [Klatt and Klatt, J. Acoust. Soc. Am. 87(2), 820–857 (1990)]. A loudness model can be used to determine the extent to which AH masks the harmonic components in voice. The resulting “partial loudness” (PL) and loudness of AH [“noise loudness” (NL)] have been shown to be good predictors of perceived breathiness [Shrivastav and Sapienza, J. Acoust. Soc. Am. 114(1), 2217–2224 (2003)]. The levels of AH and OQ were systematically manipulated for ten synthetic vowels. Perceptual judgments of breathiness were obtained and regression functions to predict breathiness from the ratio of NL to PL (η) were derived. Results show that breathiness can be modeled as a power function of η. The power parameter of this function appears to be affected by the fundamental frequency of the vowel. A second experiment was conducted to determine if the resulting power function could estimate breathiness in a different set of voices. The breathiness of these stimuli, both natural and synthetic, was determined in a listening test. The model estimates of breathiness were highly correlated with perceptual data but the absolute predicted values showed some discrepancies.